Day a novel - Cunningham, Michael 1952- (Random House, 2023)
"April 5th, 2019: In a cozy brownstone in Brooklyn, the veneer of domestic bliss is beginning to crack. Dan and Isabel, troubled husband and wife, are both a little bit in love with Isabel's younger brother, Robbie. Robbie, wayward soul of the family, who still lives in the attic loft; Robbie, who, trying to get over his most recent boyfriend, has created a glamorous avatar online; Robbie, who now has to move out of the house--and whose departure threatens to break the family apart. And then there is Nathan, age ten, taking his first uncertain steps toward independence, while Violet, five, does her best not to notice the growing rift between her parents. April 5th, 2020: As the world goes into lockdown, the brownstone is feeling more like a prison. Violet is terrified of leaving the windows open, obsessed with keeping her family safe. Isabel and Dan communicate mostly in veiled jabs and frustrated sighs. And beloved Robbie is stranded in Iceland, alone in a mountain cabin with nothing but his thoughts--and his secret Instagram life--for company. April 5th, 2021: Emerging from the worst of the crisis, the family reckons with a new, very different reality--with what they've learned, what they've lost, and how they might go on"--
Keywords: COVID-19 Pandemic, 2020- / Fiction; Curfews / Fiction; Spouses / Fiction; Marital conflict / Fiction; Families / Fiction; Couvre-feu / Romans, nouvelles, etc; Conjoints / Romans, nouvelles, etc; Familles / Romans, nouvelles, etc; Pandémie de COVID-19, 2020- / Romans, nouvelles, etc; Conflits conjugaux / Romans, nouvelles, etc; Families; Married people; Life change events / Fiction; COVID-19 (Disease) / Fiction; Brooklyn (New York, N.Y.) / Fiction; New York (N.Y.) / Fiction; Since 2020; Domestic fiction; Novels; Romans